Abnormal Topological Network in Parkinson’s Disease With Impulse Control Disorders: A Resting-State Functional Magnetic Resonance Imaging Study - Zhu, Xiaopeng; Liu, Langsha; Xiao, Yan; Li, Fan; Huang, Yongkai; Han, Deqing; Yang, Chun; Pan, Sian (Frontiers in Neuroscience, 2021)
In recent years, neuroimaging evidence shows that the brains of Parkinson’s disease (PD) with Impulse Control Disorders (ICD) patients have functional disconnection changes. However, so far, it is still unclear whether the topological organization is damaged in PD patients with ICD. In this study, we aimed to explore the functional brain network in 18 PD patients with ICD (PD-ICD), 18 PD patients without ICD(PD-nICD) by using functional magnetic resonance imaging (fMRI) and graph theory approach. We found that the PD-ICD patients had increased clustering coefficient and characteristic path length, while decreased small-world index compared with PD-nICD patients. Furthermore, we explored the hypothesis that whether the abnormality of the small-world network parameters of PD-ICD patients is accompanied by the change of nodal centrality. As we hypothesized, the nodal centralities of default mode network (DMN), control network (CN), dorsal attention network (DAN) were found to be significantly damaged in PD-ICD group compared with PD-nICD group. Our study provides more evidence for PD-ICD patients' brain network abnormalities from the perspective of information exchange, which may be the underlying pathophysiological basis of brain abnormalities in PD-ICD patients.